The Urhobo progressive Union in Nigeria, 1999 to 2024 - Prudence Tejiri Odorume; Ejiroghene Oghuvbu (Department of Accounting Universitas PGRI Yogyakarta, 2026)
The Urhobo Progressive Union (UPU), which was established to unify, represent, and advance the interests of the Urhobo people of Delta State, Nigeria, has played a significant role in fostering community cohesion, cultural preservation, and socio-economic development between 1999 and 2024. This period marked a transformative era for the UPU, characterized by adaptation to modern challenges while retaining its foundational principles. Data were gathered for the study through oral interviews, focus groups, textbooks, internet sources, journals, and unpublished theses. From 1999 to 2024, the UPU expanded its influence through strategic partnerships with governmental, non-governmental, and international organizations, focusing on advocacy for the rights and welfare of the Urhobo people of Delta State, Nigeria. The Union also played a pivotal role in addressing critical issues such as environmental degradation in the Niger Delta, youth unemployment, and the marginalization of the Urhobo people in national politics. However, challenges such as internal leadership disputes, evolving socio-political dynamics, and the need to engage younger generations tested the organization's resilience. By 2024, the UPU emerged stronger, having to redefine its strategies to remain relevant in a rapidly changing world. This study traces the UPU's journey from 1999 to 2024, highlighting its successes, challenges, and ongoing commitment to advancing the Urhobo nation. It provides a framework for understanding the union's impact and its roadmap for future progress